The influences of the fluid initial temperature and fluid flow rate to the boiling heat transfer: A short review - Faiz, Shaidan; Mohamad Firdaus, Basrawi; Ahmmad Shukrie, Md Yudin; Nurul Aini, Mohd Azman (IOP Publishing, 2025)
Recently, Low Temperature Vacuum Drying with induced Nucleation Boiling (LTVD-NB) has been studied for water reduction methods. However, low dewatering temperature led to longer drying process. Hence, to improve the LTVD-NB dewatering performance, the study on Boiling Heat Transfer (BHT) such as parameters, conditions and phenomena that may affect the heat transfer in boiling process should be understood further. Currently, some of parameters such as dewatering temperature, surface roughness, and initial water content effects in LTVD-NB have been discovered. However, the effect of the fluid initial temperature and hot water flow rate to the BHT in LTVD-NB is still unclarified. Hence, the objective of this paper is to review and examine the influences of fluid initial temperature and the effect of fluid flow rate to the BHT. In general, the result shows that the higher fluid initial temperature and flow rate significantly enhanced the BHT. As a result, the BHT in LTVD-NB system can be improved which will significantly improve the dewatering process of honey in the future.